1985
DOI: 10.3382/ps.0640871
|View full text |Cite
|
Sign up to set email alerts
|

Allometric Growth Patterns and Meat Yields of Carcass Parts of Turkey Toms as Influenced by Lighting Programs and Age

Abstract: The effects of two lighting programs and age on the meat yields and, hence, growth patterns of carcass parts in turkey toms were determined by serial slaughter experiments. Ninetysix toms were killed weekly from 15 through 26 wk of age.The low intensity step-down lighting program produced significantly heavier wings, breasts, breast muscle, percent breast muscle (P<.01) and drums (P<.05), and significantly lower percent shell and percent thigh muscle (P<.01) than the high intensity step-up lighting treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 12 publications
4
12
0
Order By: Relevance
“…This agrees with data reported by Peng et al (1985). The amounts of breast muscle at 16 and 20 wk of age were less in birds from the FL line than in individuals from the F line.…”
Section: Resultssupporting
confidence: 94%
“…This agrees with data reported by Peng et al (1985). The amounts of breast muscle at 16 and 20 wk of age were less in birds from the FL line than in individuals from the F line.…”
Section: Resultssupporting
confidence: 94%
“…As time progressed, wing yield from both sexes and drudthigh yield from males declined (Table 5). This finding was in accord with that of other investigators who reported that for males, (1) wing and thigh parts matured earlier than the breast part and (2) yield of meat from wing, drum and thigh (expressed as percent of chilled carcass weight) decreased from 15 to 26 weeks (Peng et al 1985). Drudthigh yield from females did not change over time (Table 5).…”
Section: Effect Of Sex and Age Combined With Level Of Supplemental Fasupporting
confidence: 94%
“…Carcass yields were determined as described by Wesley et al (1981) and Peng et al (1985) on birds from all dietary treatments except tiiose of the low plane diet (Diet 6). Carcass yields were not determined on birds fed the low plane diet (Diet 6) because of reduced market weights noted in the companion paper (Hester et al, 1990).…”
Section: Methodsmentioning
confidence: 99%